Frequency of Genital Infections According to Body Mass Index in Dapagliflozin-treated Patients with Type 2 Diabetes Mellitus - Rudofsky, Gottfried; Haenni, Tanja; Xu, John; Johnsson, Eva (Experimental and Clinical Endocrinology & Diabetes Reports, 2017)
Genital infections are associated with sodium glucose co-transporter 2 inhibitors such as dapagliflozin. Since patients with Type 2 diabetes are at increased risk of genital infections, and obesity is a risk factor for infections, obese patients with Type 2 diabetes could be more susceptible to genital infections when treated with sodium glucose co-transporter 2 inhibitors. This pooled dataset assessed the frequency of genital infections according to baseline body mass index in patients treated with dapagliflozin 10 mg. Data were pooled from 13 studies of up to 24 weeks’ duration (dapagliflozin N=2 360; placebo N=2 295). Frequency of genital infections was compared between three body mass index subgroups (<30, ≥30−< 35 and ≥35 kg/m2). Genital infections were reported in 130 (5.5%) patients receiving dapagliflozin and 14 (0.6%) patients receiving placebo; none of which were serious. Genital infections were more common in women (84/130 [64.6%]) than in men (46/130 [35.4%]) treated with dapagliflozin. In the body mass index < 30, ≥ 30−< 35 and ≥ 35 kg/m2 dapagliflozin-treated subgroups, 38/882 (4.3%), 47/796 (5.9%) and 45/682 (6.6%) patients presented with genital infections, respectively. Although the frequency was low overall and relatively similar between subgroups, there was a trend towards an increase in genital infections in patients with a higher body mass index. This trend is unlikely to be clinically relevant or to affect suitability of dapagliflozin as a treatment option for obese patients with Type 2 diabetes, but rather should influence advice and counselling of overweight patients on prevention and treatment of genital infections.
Keywords: sodium glucose co-transporter 2 inhibitors; obesity; counselling